Forging strength in the face of adversity: How professional identity shapes Malaysian teachers’ resilience - Samsudin, Mohd Ali; Chun, Tiew Chia; Ying, Liu, Ying; Jayathilagaratnam, Jeya Sarkunan a/l; Muniandy, Darshnee a/p (International Journal of Innovative Research and Scientific Studies, 2025)
This quantitative exploratory study delves into the perceptions of Malaysian teachers, investigating the interplay between three dimensions of teacher professional identity and the dual forces of intrinsic and extrinsic motivation in fortifying their resilience against the multifaceted challenges of teaching in public schools. Employing a cross-sectional research design, data were collected from 797 teachers through a structured questionnaire. The data were analyzed using the PLS-SEM approach for direct paths and mediation analysis. The findings underscore the pivotal role of both intrinsic and extrinsic motivation in shaping teacher professional identity, while highlighting that teachers’ resilience in the face of adversity is significantly reinforced when nurtured by both personal and institutional dimensions of professional identity. These insights illuminate the intricate web of motivational and identity-driven factors that sustain teachers’ perseverance, offering critical implications for fostering a more enduring and robust teaching workforce. Motivation acts as the support behind teachers’ specific decisions and persistence, particularly their resilience in encountering teaching challenges. School leadership, including principals and administrators, plays a crucial role in fostering teacher resilience. Findings highlight that resilience is a dynamic process shaped by interactions between individuals and their environment, emphasizing the need for supportive leadership practices to enhance teacher well-being and retention.